Hubungan Tingkat Pengetahuan dengan Sikap dalam Menjalani Terapi Diabetes Melitus Pada Penderita Diabetes Melitus di Ruang Sedap Malam RSUD Gambiran Kota Kediri - Rickiy Akbaril Okta Firdaus; Ucik Indrawati; Agus Nurul Hidayah; Agus Muslim; Afif Hidayatul Arham (Universitas Pahlawan Tuanku Tambusai, 2026)
In the hospital room Tuberose Gambiran average knowledge of patients hospitalized with less so that the influence attitude formation process. The purpose of this study was to determine the level of knowledge of the attitudes of patients with diabetes mellitus in the therapy of diabetes mellitus. This study is correlational cross-sectional research design and sampling techniques Acidental. The population in this study were patients with diabetes mellitus who were in the hospital tuberose Gambiran Kediri and obtained a sample of 15 people. This study used statistical test chi - square with significance level α = 0.05. Retrieval of data using questionnaires. The independent variable in this study is the level of knowledge, while the dependent variable is the attitude in the therapy of diabetes mellitus. Based on the results of research to the level of knowledge acquired 11 respondents (73.3%) had less knowledge, 3 respondents (20%) had sufficient knowledge and one respondent (6.7%) had good knowledge. For attitudes in therapy of diabetes mellitus obtained 12 respondents (80%) had a negative attitude and a third of respondents (20%) had a positive attitude. After statistical test chi - Square with values ​​obtained α = 0.05 p = 0.001 H0 rejected indicating that there is a level of knowledge with attitude in therapy of diabetes mellitus in patients with diabetes mellitus in public hospitals tuberose Gambiran Kediri. Based on this study it is expected that people with diabetes to seek information about the disease so that he could know about the disease diabetes mellitus so that he could be positive in therapy. Keywords: Knowledge, Attitude, Diabetes Mellitus